Titanium dioxide composite sunscreen material based on silicon microsphere modification and preparation method thereof
By loading titanium dioxide on the surface of high-surface charge silica microspheres, forming a titanium dioxide composite sunscreen material based on silicon microsphere modification, solving the problems of poor skin feeling and safety risks of existing titanium dioxide sunscreens, achieving efficient and safe sunscreen effects.
Patent Information
- Application Number
- CN202510082980.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-18
- Publication Date
- 2025-04-25
AI Technical Summary
In actual applications, existing physical sunscreens of titanium dioxide have problems such as poor skin feeling, dispersion and insufficient sealing, and small nanoparticle size leads to safety risks.
By loading the distribution of titanium dioxide on the surface of high-surface charge silica microspheres, a titanium dioxide composite sunscreen material based on silicon microspheres is formed to improve the absorption value of the UVB band and improve the skin feeling.
It has achieved light skin feeling, good sun protection performance, low cost and good biocompatibility, overcomes the safety risks caused by poor skin feeling and small nanoparticle size, and has improved sun protection performance by nearly 15 times.
Smart Images

Figure CN119868172A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of cosmetics, and in particular to a titanium dioxide composite sunscreen material modified by silicon microspheres and a preparation method thereof. Background Art
[0002] Titanium dioxide (TiO 2 ) is one of the only physical sunscreens approved for use in my country. It is a broad-spectrum sunscreen that has a strong shielding ability mainly for the UVB band (280-320nm) and also has the ability to protect the UVA band (320-400nm). It also has stable chemical properties, antibacterial properties, ultraviolet reflection, non-toxicity, high transparency and other characteristics. It is mild and non-irritating to the skin, so it is widely used as an additive in sunscreen cosmetics.
[0003] Although it has outstanding applicability in the field of sun protection, there are still certain defects in actual application: first, titanium dioxide is used as a physical sunscreen. If it is to provide a good sun protection effect, the dosage must reach 10%-20%, which will form a thicker white coating with an obvious "fake white feeling" and has disadvantages such as poor dispersibility, closure and poor skin feel, which is prone to "white sweat" or greasy and airtight skin; second, nano titanium dioxide has a small particle size, usually 1nm-100nm, and the diameter of human pores is about 6μm. The use of cosmetics added with nano titanium dioxide is prone to cause adverse reactions such as clogging pores, inhalation or penetration into skin tissue, causing skin inflammation and is not easy to be eliminated with sweat, and there are certain safety risks in use. Summary of the invention
[0004] The purpose of the present invention is to provide a titanium dioxide composite sunscreen material based on silicon microsphere modification and a preparation method thereof, which can double the absorption value of the composite sunscreen material in the UVB band, and provide a light skin feel, effectively overcoming the shortcomings of nano titanium dioxide, such as poor skin feel and poor safety due to small nanoparticle size. Titanium dioxide is distributed on the surface of silicon dioxide microspheres (SNS) with high surface charge and good dispersion, which has the advantages of light skin feel, good sunscreen performance, low cost, and good biocompatibility.
[0005] In order to achieve the above object, the technical solution of the present invention is as follows:
[0006] On the one hand, the present invention provides a titanium dioxide composite sunscreen material modified based on silica microspheres, wherein the titanium dioxide composite sunscreen material modified based on silica microspheres uses monodisperse silica microspheres with high surface charge as carriers, and titanium dioxide is uniformly distributed on the surface of the silica microspheres.
[0007] Furthermore, the silica microspheres are submicronized particles with a particle size of about 300-450 nm.
[0008] Furthermore, the particle size of the titanium dioxide composite sunscreen material modified by silicon microspheres is about 300-500 nm.
[0009] Furthermore, the dispersibility of the silica microspheres is 0.2-0.3.
[0010] Furthermore, the titanium dioxide composite sunscreen material modified by silica microspheres has titanium dioxide uniformly distributed on the surface of the silica microspheres, and the loading amount of the metal element titanium is 1.0-6.5 wt %.
[0011] In a second aspect, the present invention further provides a method for preparing the aforementioned titanium dioxide composite sunscreen material based on modified silicon microspheres, comprising the following steps:
[0012] S1. Providing silica microspheres, wherein the silica microspheres are monodisperse silica microspheres with high surface charge, which are prepared by reacting citric acid, ammonia, tetraethyl orthosilicate, and a solvent as raw materials;
[0013] S2. Prepare a titanium dioxide composite sunscreen material modified based on silica microspheres, which is prepared by reacting the silica microspheres, ammonia water, ethyl acetate, and tetrabutyl titanate as raw materials.
[0014] Furthermore, the preparation steps of the silica microspheres include:
[0015] S11. Mixing citric acid and ethanol to obtain solution A, then mixing solution A with aqueous ammonia to obtain solution B; mixing tetraethyl orthosilicate with ethanol to obtain solution C;
[0016] S12. Add solution C dropwise into solution B to obtain suspension D after a period of reaction. After centrifugation, washing and drying, silica microspheres are obtained.
[0017] Furthermore, the amount of citric acid added is 0.2 g, and the amount of anhydrous ethanol is 100 mL;
[0018] Preferably, the concentration of the ammonia water is 25% and the amount added is 24 mL;
[0019] Preferably, the reaction time of the solution A and the ammonia water is 0.5 h; preferably, the amount of ethyl orthosilicate added is 9 mL, and the amount of anhydrous ethanol added is 50 mL;
[0020] Preferably, the mixing reaction time of ethyl orthosilicate and ethanol is 0.5h;
[0021] Preferably, the reaction time of the solution C and the solution B is 2.5h;
[0022] Preferably, the drying temperature is 55°C-80°C.
[0023] Furthermore, the preparation steps of the titanium dioxide composite sunscreen material modified by silicon microspheres include:
[0024] S21. The silica microspheres are mixed with aqueous ammonia to obtain a suspension E, which is centrifuged to obtain a white precipitate F, and then the white precipitate F is mixed with ethyl acetate to obtain a suspension G;
[0025] S22. Tetrabutyl titanate is mixed with ethyl acetate to obtain solution H, and then solution H is mixed with suspension G to react to obtain suspension I. After suction filtration, washing and drying, a titanium dioxide composite sunscreen material modified by silicon microspheres is obtained.
[0026] Furthermore, the amount of silica microspheres added is 1.2 g, the concentration of ammonia water is 0.6 mol / L and the amount added is 12 mL;
[0027] Preferably, the mixing reaction time of the silica microspheres and ammonia water is 15 minutes;
[0028] Preferably, the white precipitate F is mixed with 38 mL of ethyl acetate;
[0029] Preferably, the amount of butyl titanate added is 0.6 mL, and the amount of ethyl acetate added is 2 mL;
[0030] Preferably, the solution H and the suspension G are mixed and reacted for 3 hours;
[0031] Preferably, the drying temperature is 105°C.
[0032] The present invention firstly uses citric acid (CA), ammonia water (NH 3 ·H 2 Silica microspheres (SNS) with high surface charge and good dispersibility were prepared by chemical precipitation method using tetraethyl orthosilicate (TEOS) and tetraethyl orthosilicate (TEOS) as raw materials. Citric acid and ammonia water were introduced into the synthesis process to form a buffer pair, forming a pH environment suitable for the generation of monodisperse silica microspheres. At the same time, a certain amount of carboxyl groups were introduced into the surface of the silica microspheres (SNS) to have high surface charge. Due to the repulsive effect between the surface charges, the silica microspheres (SNS) have good dispersibility. The whole preparation process is simple, energy-saving and environmentally friendly.
[0033] Secondly, in an alkaline environment, in a suspension system composed of silica microspheres (SNS) and a dispersion medium (ethyl acetate), namely, in a "SNS+ethyl acetate" suspension system, butyl titanate undergoes hydrolysis at the "solid / liquid" interface, producing Ti(OH) 4The titanium dioxide was loaded on the surface of the silica microspheres, and after high-temperature drying, the surface of the silica microspheres was loaded with titanium dioxide to obtain a titanium dioxide composite sunscreen material based on silica microspheres modified (SNS@TiO 2 Specifically, the present invention utilizes the highly active carboxyl groups introduced on the surface of silica microspheres (SNS) as active sites, and in the suspension system composed of "SNS+ethyl acetate", Ti(OH) 4 The hydroxyl groups in the Ti(OH) 4 Secondary deposition on the surface of silica microspheres (SNS) and the adjustment of appropriate alkaline conditions can promote the polycondensation process to be more stable, making Ti(OH) generated by hydrolysis of butyl titanate 4 The titanium dioxide is loaded on the surface of the silica microspheres (SNS) relatively evenly, and then washed and dried at high temperature to load the titanium dioxide on the surface of the silica microspheres (SNS) to obtain a titanium dioxide composite sunscreen material based on silica microspheres modified (SNS@TiO 2 ).
[0034] Beneficial effects of the present invention:
[0035] The present invention uses silica microspheres (SNS) with high surface charge and good dispersion as carriers, and effectively regulates the loading amount and morphology of titanium dioxide on the surface of silica microspheres (SNS), thereby regulating the sunscreen effect of the composite sunscreen material, and obtains a titanium dioxide composite sunscreen material (SNS@TiO 2 ), and the preparation method thereof is simple to operate and is green and environmentally friendly.
[0036] The present invention is based on the titanium dioxide composite sunscreen material modified by silicon microspheres (SNS@TiO 2 ) By combining silica microspheres, that is, submicron (particle size of 300-500nm) silica microspheres with titanium dioxide, the refractive index of titanium dioxide is increased, and the sunscreen performance is improved. It not only improves the skin feel, but also increases the particle size, has high safety, has the advantages of light skin feel, good sunscreen performance, low cost, and good biocompatibility, overcomes the shortcomings of titanium dioxide such as poor skin feel and poor safety due to small nanoparticle size, has a light skin feel, is thin and not heavy, and retains good sunscreen performance to meet the needs of users. When the titanium dioxide composite sunscreen material modified by silica microspheres (SNS@TiO 2 ) is about 6.5wt%, its sunscreen performance is better than that of traditional sunscreen products (such as pure TiO 2 ) increased by nearly 15 times, with high physical and chemical stability and excellent comprehensive performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 The SNS and SNS@TiO 2 SEM images of
[0038] Figure 2 The SNS and TiO 2 and SNS@TiO 2 IR spectrum of
[0039] Figure 3 The SNS and TiO 2 and SNS@TiO 2 XRD pattern of
[0040] Figure 4 The SNS and SNS@TiO 2 、TiO 2 UV spectrum;
[0041] Figure 5 The SNS@TiO prepared by the present invention with different amounts of butyl titanate 2 UV spectrum;
[0042] Figure 6 The SNS@TiO prepared by the present invention with different ammonia concentrations 2 Schematic diagram of particle size analysis. DETAILED DESCRIPTION
[0043] The embodiments of the present invention are described in detail below.
[0044] The specific implementation steps of the present invention are divided into two steps:
[0045] S1. Providing silica microspheres, wherein the silica microspheres are monodisperse silica microspheres with high surface charge, which are prepared by reacting citric acid, ammonia, tetraethyl orthosilicate, and a solvent as raw materials;
[0046] S2. Prepare a titanium dioxide composite sunscreen material modified based on silica microspheres, which is prepared by reacting the silica microspheres, ammonia water, ethyl acetate, and tetrabutyl titanate as raw materials.
[0047] First, the preparation of silica microspheres (SNS) was carried out, using citric acid (CA), ammonia (NH3·H2O) and tetraethyl orthosilicate (TEOS) as raw materials. During the synthesis process, citric acid and ammonia formed a buffer pair, forming a suitable alkaline environment, which promoted the relatively controllable hydrolysis reaction of tetraethyl orthosilicate (TEOS) to generate silica particles with moderate particle size and good dispersibility. Secondly, the titanium dioxide composite sunscreen material SNS@TiO2 modified by silica microspheres was synthesized. 2In the suspension system composed of "SNS + ethyl acetate", under weak alkaline conditions, at the "solid / liquid" interface, the carboxyl active groups on the surface of the silica microspheres are used as active sites to condense and combine with the hydroxyl groups in Ti(OH)4 to form Ti(OH) 4 The secondary deposition is loaded on the surface of silicon microspheres and transformed into TiO after washing and high-temperature drying. 2 The surface of the silica microspheres was loaded to prepare the titanium dioxide composite sunscreen material SNS@TiO 2 .
[0048] Example 1
[0049] This embodiment provides silica microspheres (SNS) and a preparation method thereof, the specific steps comprising:
[0050] 1) Dissolve 0.2 g of citric acid in 100 mL of anhydrous ethanol to obtain solution A;
[0051] 2) Dissolve 24 mL of aqueous ammonia (the concentration of aqueous ammonia is 25 wt%) in solution A and react for 0.5 h to obtain solution B;
[0052] 3) Dissolve 9 mL of tetraethyl orthosilicate in 50 mL of anhydrous ethanol and react for 0.5 h to obtain solution C;
[0053] 4) Add solution C dropwise into solution B and react for 2.5 h to obtain suspension D;
[0054] 6) The suspension D was centrifuged at 8000 r / min, washed twice with 100 mL of pure water and once with 100 mL of anhydrous ethanol, and dried at 80° C. to obtain silica microspheres, which were stored for later use.
[0055] Example 2
[0056] This embodiment provides silica microspheres (SNS) and a preparation method thereof. The specific steps are basically the same as those in Example 1, except that the amount of citric acid is changed. The specific steps are as follows:
[0057] 1) Dissolve 0.4 g of citric acid in 100 mL of anhydrous ethanol to obtain solution A;
[0058] The resulting suspension D was centrifuged, washed, and dried at 55°C to obtain silica microspheres, which were then stored for later use.
[0059] Example 3
[0060] This embodiment provides silica microspheres (SNS) and a preparation method thereof. The specific steps are basically the same as those in Example 1, except that the amount of citric acid is changed. The specific steps are as follows:
[0061] 1) Dissolve 0.6 g of citric acid in 100 mL of anhydrous ethanol to obtain solution A;
[0062] The resulting suspension D was centrifuged, washed, and dried at 65°C to obtain silica microspheres, which were then stored for later use.
[0063] The above Examples 1-3 all generate silica microspheres (SNS) with moderate particle size and good dispersibility. The silica microspheres are submicron particles with a particle size of about 300-450 nm. The dispersibility of the silica microspheres is 0.2-0.3. A certain amount of carboxyl groups are introduced on the surface of the silica microspheres (SNS) to have a high surface charge. Due to the repulsive effect between the surface charges, the silica microspheres (SNS) have good dispersibility. The entire preparation process is simple, consumes less energy, and is green and environmentally friendly.
[0064] Example 4
[0065] This embodiment provides a titanium dioxide composite sunscreen material SNS@TiO based on silicon microspheres modified 2 And a preparation method thereof, the specific steps include:
[0066] 1) 1.2 g of silica microspheres SNS (using Example 1 as an example) were dispersed in 12 mL of 0.1 M ammonia water (i.e., the concentration of ammonia water was 0.1 mol / L), and stirred for 15 min to obtain a suspension E;
[0067] 2) Centrifuge the suspension E at 5000 r / min to remove the ammonia solution and obtain a relatively moist white precipitate F;
[0068] 3) Add the white precipitate F into 38 mL of ethyl acetate to obtain solution G;
[0069] 4) dissolving 0.6 mL of tetrabutyl titanate in 2 mL of ethyl acetate to obtain solution H;
[0070] 5) Add solution H to solution G, stir and react for 3 h to obtain suspension I;
[0071] 6) The suspension I was filtered, washed twice with 100 mL of pure water, washed once with 100 mL of anhydrous ethanol, and dried at 105° C. to obtain a titanium dioxide composite sunscreen material SNS@TiO2 modified by silicon microspheres. 2 .
[0072] Example 5
[0073] This embodiment provides a titanium dioxide composite sunscreen material SNS@TiO based on silicon microspheres modified 2 The specific steps are basically the same as those in Example 4, except that the concentration of ammonia water is changed. The specific steps are as follows:
[0074] 1) Disperse 1.2 g of SNS in 12 mL of 0.2 M ammonia solution and stir for 15 min to obtain suspension E.
[0075] Example 6
[0076] This embodiment provides a titanium dioxide composite sunscreen material SNS@TiO based on silicon microspheres modified 2 The specific steps are basically the same as those in Example 4, except that the concentration of ammonia water is changed. The specific steps are as follows:
[0077] 1) Disperse 1.2 g of SNS in 12 mL of 0.4 M ammonia solution and stir for 15 min to obtain suspension E.
[0078] Example 7
[0079] This embodiment provides a titanium dioxide composite sunscreen material SNS@TiO based on silicon microspheres modified 2 The specific steps are basically the same as those in Example 4, except that the concentration of ammonia water is changed. The specific steps are as follows:
[0080] 1) Disperse 1.2 g of SNS in 12 mL of 0.6 M ammonia solution and stir for 15 min to obtain suspension E.
[0081] Example 8
[0082] This embodiment provides a titanium dioxide composite sunscreen material SNS@TiO based on silicon microspheres modified 2 The specific steps are basically the same as those in Example 4, except that the concentration of ammonia water is changed. The specific steps are as follows:
[0083] 1) Disperse 1.2 g of SNS in 12 mL of 0.8 M ammonia solution and stir for 15 min to obtain suspension E.
[0084] Example 9
[0085] This embodiment provides a titanium dioxide composite sunscreen material SNS@TiO based on silicon microspheres modified 2 The specific steps are basically the same as those in Example 4, except that the concentration of ammonia water is changed. The specific steps are as follows:
[0086] 1) Disperse 1.2 g of SNS in 12 mL of 1.0 M ammonia solution and stir for 15 min to obtain suspension E.
[0087] Example 10
[0088] This embodiment provides a titanium dioxide composite sunscreen material SNS@TiO based on silicon microspheres modified 2The specific steps are basically the same as those in Example 7, except that the amount of tetrabutyl titanate is changed. The specific steps are as follows:
[0089] 4) 0.05 mL of tetrabutyl titanate was dissolved in 2 mL of ethyl acetate to obtain solution H.
[0090] Embodiment 11
[0091] This embodiment provides a titanium dioxide composite sunscreen material SNS@TiO based on silicon microspheres modified 2 The specific steps are basically the same as those in Example 7, except that the amount of tetrabutyl titanate is changed. The specific steps are as follows:
[0092] 4) 0.1 mL of tetrabutyl titanate was dissolved in 2 mL of ethyl acetate to obtain solution H.
[0093] Example 12
[0094] This embodiment provides a titanium dioxide composite sunscreen material SNS@TiO based on silicon microspheres modified 2 The specific steps are basically the same as those in Example 7, except that the amount of tetrabutyl titanate is changed. The specific steps are as follows:
[0095] 4) 0.2 mL of tetrabutyl titanate was dissolved in 2 mL of ethyl acetate to obtain solution H.
[0096] Example 13
[0097] This embodiment provides a titanium dioxide composite sunscreen material SNS@TiO based on silicon microspheres modified 2 The specific steps are basically the same as those in Example 7, except that the amount of tetrabutyl titanate is changed. The specific steps are as follows:
[0098] 4) 0.3 mL of tetrabutyl titanate was dissolved in 2 mL of ethyl acetate to obtain solution H.
[0099] Embodiment 14
[0100] This embodiment provides a titanium dioxide composite sunscreen material SNS@TiO based on silicon microspheres modified 2 The specific steps are basically the same as those in Example 7, except that the amount of tetrabutyl titanate is changed. The specific steps are as follows:
[0101] 4) 0.4 mL of tetrabutyl titanate was dissolved in 2 mL of ethyl acetate to obtain solution H.
[0102] Embodiment 15
[0103] This embodiment provides a titanium dioxide composite sunscreen material SNS@TiO based on silicon microspheres modified 2The specific steps are basically the same as those in Example 7, except that the amount of tetrabutyl titanate is changed. The specific steps are as follows:
[0104] 4) 0.6 mL of tetrabutyl titanate was dissolved in 2 mL of ethyl acetate to obtain solution H.
[0105] The titanium dioxide composite sunscreen material modified by silicon microspheres prepared in the above-mentioned Examples 4-15 uses monodisperse silicon dioxide microspheres with high surface charge as carriers, and titanium dioxide is uniformly distributed on the surface of the silicon dioxide microspheres. The particle size of the titanium dioxide composite sunscreen material modified by silicon microspheres is about 300-500nm, and the loading amount of titanium dioxide and the metal element titanium in the titanium dioxide composite sunscreen material modified by silicon microspheres is 1-6.5wt%. Because Examples 4-15 exemplarily study the effects of the amount of tetrabutyl titanate, ammonia concentration, etc. on the performance of SNS@TiO2, wherein the titanium content corresponding to Example 15 is 6.5%, and the preferred amount of butyl titanate is 0.6mL; when the amount of butyl titanate is greater than 0.6mL, the skin feel of the product is significantly deteriorated, and when the amount of butyl titanate is less than 0.1mL, the UVB band absorption value of the product is too low.
[0106] The present invention is to prepare the SNS and SNS@TiO 2 To test:
[0107] The composite sunscreen material SNS@TiO 2 The suspension is prepared into a suitable concentration, and its sunscreen performance is measured by ultraviolet spectrophotometer.
[0108] By the attached Figure 1 It can be seen that SNS and SNS@TiO 2 Under the microscopic view, the SNS@TiO 2 There is also metal element titanium attached to the surface, with a particle size of about 400nm. Compared with SNS, SNS@TiO 2 The shape of SNS@TiO is basically regular spherical, indicating that 2 It has a good skin feel, soft and delicate.
[0109] By the attached Figure 2 It can be seen that the bending vibration peak of TiO2 at 1441cm-1 is Ti-OH, while the peak of SNS@TiO2 at 1445cm-1 is stronger than that of SNS. 2 There is also an absorption peak at 928 cm-1, while SNS has no absorption peak in this range. The above shows that TiO 2 With SiO 2 Bonding occurs between the two, and Ti-O-Si bonds appear, resulting in the composite sunscreen material SNS@TiO 2 .
[0110] By the attached Figure 3 It can be seen that SNS, TiO 2 and SNS@TiO 2 In the XRD spectrum, red is SiO 2 , blue is SNS@TiO 2 , black is homemade TiO 2 , PDF#21-1272 is a traditional pure TiO 2 Standard card, pure TiO 2 The XRD pattern of traditional pure TiO 2 The corresponding specific lattice peaks in SNS@TiO 2 The XRD pattern of the traditional pure TiO 2 The corresponding lattice peaks prove that secondary deposition occurs on the surface of the silica microspheres and titanium dioxide is loaded on the silica microspheres SiO 2 The surface has a new phase different from traditional pure TiO2, that is, SNS@TiO2 with excellent sun protection performance is prepared.
[0111] Attached Figure 4 The meaning of "SNS-1.0" in the test is that the amount of SNS sample used in the test is 1.0 mg / mL. Figure 4 It can be seen that when the absorbance of the sample SNS@TiO2 in the UVB band (280-320nm) is at least higher than 1 and the absorbance in the UVA band (320-400nm) is at least higher than 0.5, the sample is considered to have sunscreen properties. In a 0.5% chitosan solution prepared with 0.1% glacial acetic acid as solvent, Figure 4 1.0 means the test concentration of the test sample is 1 mg / mL, 0.065 means 0.065 mg / mL, and only for each test sample SNS, TiO 2 、SNS@TiO 2 The test concentration of pure SNS was proved to be effective for the sample (SNS@TiO 2 ) has no significant effect on sunscreen performance, which is not the reason for the improvement of sunscreen performance, and SNS, TiO 2 、SNS@TiO 2 At the same concentration (1 mg / mL), the sample (SNS@TiO 2 ) and TiO 2 The sun protection performance of the samples (SNS@TiO 2 ) The actual titanium loading is only 6.5wt%, i.e., 1mg SNS@TiO 2 The sample contained 0.065 mg of pure TiO 2, the concentration of titanium dioxide contained was obtained at the same dilution multiple (0.065 mg / mL). By comparing the sunscreen performance and concentration of titanium dioxide with the same performance and content, it was concluded that 1 mg sample (SNS@TiO 2 ) Compared with pure titanium dioxide, the amount of titanium dioxide used is less (0.065mg), but it has the sun protection performance of 1mg pure titanium dioxide, achieving a 15.4-fold increase in sun protection performance.
[0112] Attached Figure 5 The test samples are all composite sunscreen material samples, where "0.6-1.0" means: when testing, the sample of Example 15 is selected as an example, the amount of butyl titanate used in the synthesis is "0.6mL", and the amount of the sample used in the test is 1.0mg / mL, which is marked as "0.6-1.0" accordingly. Figure 5 and attached Figure 6 It can be seen that when the sample SNS@TiO 2 The sample is considered to have sunscreen properties if the absorbance in the UVB band (280-320nm) is at least higher than 1 and the absorbance in the UVA band (320-400nm) is at least higher than 0.5. In a 0.5% chitosan solution prepared with 0.1% glacial acetic acid as solvent, when the concentration of the sample is 1 mg / mL, for example, the SNS@TiO prepared with 0.6 mL of butyl titanate 2 The absorbance is high, and the ammonia concentration is preferred, the PDI value is low, and the particle size distribution is relatively uniform at about 400nm. In the suspension system composed of "SNS + ethyl acetate", under weak alkaline conditions, at the "solid / liquid" interface, the carboxyl active groups on the surface of the silica microspheres are used as active sites, and Ti(OH) 4 The hydroxyl groups in the Ti(OH) 4 The secondary deposition is loaded on the surface of the silicon microspheres and after washing and high temperature drying, it is transformed into TiO 2 After loading, a composite sunscreen material SNS@TiO is formed. 2 Since there are highly active carboxyl groups on the surface of silica microspheres SNS, changing the concentration of ammonia water to adjust the pH environment is conducive to the formation of SNS@TiO 2 The dispersion is better and the particle size is more uniform. By changing the amount of butyl titanate, the loading amount of titanium dioxide on the surface of the silicon microspheres can be increased, which is beneficial to improve the sample (SNS@TiO 2 ) sunscreen performance. By changing the concentration of ammonia water, the formation of SNS@TiO 2 In the process, under the weak alkaline condition of ammonia solution, it is beneficial to the hydrolysis of butyl titanate and promotes the reaction of Ti(OH) 4 Combined with the carboxyl active groups on the silica microspheres, a sample with a relatively uniform particle size (SNS@TiO2 ).
[0113] At the same time, the present invention is pure TiO 2 、SNS@TiO 2 To measure the ductility, 1.5 g of the composite sunscreen material (SNS@TiO 2 ) The powder was placed in a circle with a diameter of 4 cm in the center of a glass plate. A glass weighing 1 kg was placed on the glass plate for five minutes. The diameter change was recorded, the ductility was measured, and the skin feel test was performed. The test results are shown in the following table:
[0114] Table 1 shows the test results of ductility measurement
[0115]
[0116] The ductility tests of the above samples were measured 3 times, and the above "diameter" actually refers to the "extended diameter" of the sample after it was unfolded during the ductility test. Analysis of the data in Table 1 shows that: (1) Because the particle size of traditional pure TiO2 is small, the average extended diameter of the sample measured in the ductility test is 5.20 cm, and its actual skin feel evaluation is: astringent, blocked when applied, and poor skin feel. (2) However, the actual skin feel evaluation of the SNS@TiO2 sample prepared by the present invention (exemplary as Example 15) is: soft and light on the skin, easy to spread. This is mainly because: in the ductility test, the average extended diameter of the SNS@TiO2 sample is 5.50 cm. Although the test difference with the pure TiO2 sample is only 0.3 cm, the actual skin feel evaluation is significantly different: pure TiO2 has a frictional feel and is relatively astringent; while SNS@TiO2 is soft and has no astringent feeling, is smooth when applied on the skin, is comfortable to the skin, and has improved ductility. Therefore, the obvious difference in skin feel between pure TiO2 and SNS@TiO2 can be attributed to the use of a heterogeneous reaction system to prepare uniformly distributed titanium dioxide on the surface of silica microspheres through secondary hydrolysis at the interface of SNS microspheres.
[0117] The above are only specific embodiments of the present invention, and the protection scope of the present invention is not limited thereto; any replacement and improvement made on the basis of not violating the concept of the present invention shall fall within the protection scope of the present invention.
Claims
1. A titanium dioxide composite sunscreen material modified by silicon microspheres, characterized in that: The titanium dioxide composite sunscreen material based on modified silicon microspheres uses monodisperse silicon dioxide microspheres with high surface charge as carriers, and titanium dioxide is uniformly distributed on the surface of the silicon dioxide microspheres.
2. The titanium dioxide composite sunscreen material modified by silicon microspheres according to claim 1, characterized in that: The silicon dioxide microspheres are submicron particles with a particle size of 300-450nm.
3. The titanium dioxide composite sunscreen material modified by silicon microspheres according to claim 1, characterized in that: The particle size of the titanium dioxide composite sunscreen material modified by silicon microspheres is 300-500nm.
4. The titanium dioxide composite sunscreen material modified by silicon microspheres according to claim 1, characterized in that: The dispersibility of the silicon dioxide microspheres is 0.2-0.
3.
5. The titanium dioxide composite sunscreen material modified by silicon microspheres according to claim 1, characterized in that: The titanium dioxide composite sunscreen material modified by silicon microspheres has titanium dioxide uniformly distributed on the surface of the silicon dioxide microspheres, and the loading amount of the metal element titanium is 1-6.5wt%.
6. A method for preparing a titanium dioxide composite sunscreen material modified with silicon microspheres according to any one of claims 1 to 5, characterized in that: The steps include: S1. Providing silica microspheres, wherein the silica microspheres are monodisperse silica microspheres with high surface charge, which are prepared by reacting citric acid, ammonia, tetraethyl orthosilicate, and a solvent as raw materials; S2. Prepare a titanium dioxide composite sunscreen material modified based on silica microspheres, which is prepared by reacting the silica microspheres, ammonia water, ethyl acetate, and tetrabutyl titanate as raw materials.
7. The method for preparing a titanium dioxide composite sunscreen material modified by silicon microspheres according to claim 6, characterized in that: The preparation steps of the silica microspheres include: S11. Mixing citric acid and ethanol to obtain solution A, then mixing solution A with aqueous ammonia to obtain solution B; mixing tetraethyl orthosilicate with ethanol to obtain solution C; S12. Add solution C dropwise into solution B to obtain suspension D after a period of reaction. After centrifugation, washing and drying, silica microspheres are obtained.
8. The method for preparing a titanium dioxide composite sunscreen material modified by silicon microspheres according to claim 7, characterized in that: The added amount of citric acid is 0.2-0.6 g, and the amount of anhydrous ethanol is 100 mL; Preferably, the concentration of the ammonia water is 25% and the amount added is 24 mL; Preferably, the reaction time of solution A and ammonia water is 0.5h; Preferably, the amount of tetraethyl orthosilicate added is 9 mL, and the amount of anhydrous ethanol added is 50 mL; preferably, the mixing reaction time of tetraethyl orthosilicate and ethanol is 0.5 h; Preferably, the reaction time of the solution C and the solution B is 2.5h; Preferably, the drying temperature is 55°C-80°C.
9. The method for preparing a titanium dioxide composite sunscreen material modified by silicon microspheres according to claim 6, characterized in that: The steps for preparing the titanium dioxide composite sunscreen material modified by silicon microspheres include: S21. The silica microspheres are mixed with aqueous ammonia to obtain a suspension E, which is centrifuged to obtain a white precipitate F, and then the white precipitate F is mixed with ethyl acetate to obtain a suspension G; S22. Tetrabutyl titanate is mixed with ethyl acetate to obtain solution H, and then solution H is mixed with suspension G to react to obtain suspension I. After filtration, washing and drying, a titanium dioxide composite sunscreen material modified by silicon microspheres is obtained.
10. The method for preparing a titanium dioxide composite sunscreen material modified by silicon microspheres according to claim 9, characterized in that: The amount of silica microspheres added is 1.2 g, the concentration of ammonia water is 0.1-1 mol / L and the amount added is 12 mL; Preferably, the mixing reaction time of the silica microspheres and ammonia water is 15 minutes; Preferably, the white precipitate F is mixed with 38 mL of ethyl acetate; Preferably, the amount of butyl titanate added is 0.05-0.6 mL, and the amount of ethyl acetate added is 2 mL; preferably, the solution H and the suspension G are mixed and reacted for 3 hours; Preferably, the drying temperature is 105°C.
Citation Information
Patent Citations
Nanometer silicon dioxide and titanium dioxide compound microparticle and preparation method thereof
CN101624188A
Preparation method for core-shell TiO2-SiO2 microsphere self-assembled structural color film
CN106423000A
Monodisperse silicon microsphere modification-based zinc oxide sunscreen material and preparation method thereof
CN118873422A
Process for preparing uniform compound monodispersed nm-class spherical TiO2 particles
CN1296917A
Titanium-silica complex and cosmetic preparation compounding the same
US6358495B1
Cited By
Titanium oxide composite sunscreen material based on mesoporous silica as well as preparation method and application of titanium oxide composite sunscreen material
CN121445629A